Impact of chitosan embedded with postbiotics from Pediococcus acidilactici against emerging foodborne pathogens in vacuum-packaged frankfurters during refrigerated storage - Incili, Gokhan Kursad; Karatepe, Pinar; Akgol, Muzeyyen; Tekin, Ali; Kanmaz, Hilal; Kaya, Busra; Hayaloglu, Ali Adnan (Elsevier Sci Ltd, 2022)
The objective of the study was to carry out characterization of postbiotics from Pediococcus acidilactici and to assess their efficacy (50% and 100%) in combination with chitosan (0.5 and 1%) against Escherichia coli O157: H7, Salmonella Typhimurium, Listeria monocytogenes on frankfurters during refrigerated storage for 35 days. High amounts of total phenolic content (1708.15 +/- 93.28 mg GAE/L) and carboxylic acids, which comprised 74.89% of the total volatiles, were found in the postbiotics. On day 0, the postbiotic-chitosan combinations decreased the E. coli O157:H7, L. monocytogenes and S. Typhimurium counts ranging from 1.58 to 3.21 log(10) compared to the control in frankfurters (P < 0.05). Total viable count and number of lactic acid bacteria were effectively reduced in all treatment groups (P < 0.05), and postbiotic and chitosan treatments did not cause any changes in pH and color of the frankfurters. In conclusion, postbiotic-chitosan combinations can be used to reduce the risks that might be associated with E. coli O157:H7, L. monocytogenes, and S. Typhimurium in frankfurters.
Keywords: Frankfurter; Postbiotic; Characterization; Chitosan; Antimicrobial effect; Chemical quality